Association Between Body Composition and Bone Mineral Density in Men on Hemodialysis. (October 2015) - Marinho, Sandra M. S. de A.; Wahrlich, Vivian; Mafra, Denise
Abstract : Abstract: Studies have revealed complex interactions between bone and fat, however there are few studies about this crosstalk in patients with chronic kidney disease. This study investigated possible relationship between bone mineral density (BMD) and body composition in patients who underwent hemodialysis. Twenty patients were enrolled in a cross-sectional study (47.0 [42.3–56.8] years, body mass index 26.0 ± 4.2 kg/m 2, dialysis vintage of 48.5 [26.7–95.7] months). Body composition and BMD were assessed by dual-energy X-ray absorptiometry. Leptin and parathormone levels were analyzed using Multiplex kits (R&D System Inc). Low bone mass in the femoral neck was reported in 54.8% of patients. Total BMD and total T-score were positively correlated with lean mass (r = 0.46, P = 0.04; r = 0.47, P = 0.04, respectively), but not with leptin or body fat mass. In conclusion, lean body mass is probably important to maintain bone health in male patients who underwent hemodialysis.